A Qualitative Analysis of Followership Behaviors among University Teachers in Balochistan : An Exploratory Study - Maula Bakhsh, Raheela; Parvez, Anjum; Ahmed, Ammarah; Farooqi, Zonia Nabil (Pakistan Business Review, 2025)
Followership behavior is an important aspect of leadership. It is believed that leadership, with followership, is nothing. That is why; this construct has gained a great deal of management researchers.  Researchers, around the globe have presented various models of followership styles or behaviors. However, this study, drawing upon the Kelly’s Model of Followership, explored the followership styles of university teachers in Balochistan, Pakistan. Due to qualitative and exploratory nature, in-depth interviews were conducted to collect data. These interviews were properly transcribed and then converted into ‘codes’ and ‘themes’ for analysis. These ‘codes’ and ‘themes’ were then matched with the styles in Kelly’s Model.  Results indicate that ‘Exemplary style’ prevails most among faculty members in HEI’s of Balochistan. In the end, certain important insights and implications are discussed.
Keywords: Followership Behaviors, University Teachers, Baluchistan.